2017
DOI: 10.20429/ger.2017.140101
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Perceptions about the Effectiveness of the TOON Comic Books in Their Guided Reading Instruction

Abstract: Recently, education and literacy researchers have acknowledged educational merit in guided reading that incorporates interactive and authentic reading texts, such as graphic novels, which meet the needs of today's predominantly multimodal learners (Jennings, Rule, & Zanden, 2014; Kist & Pytash, 2015). This qualitative study explores through interviews and a questionnaire the perceptions of pre-service teachers about the effectiveness of the comic book series known as TOON comics in guided reading with struggli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Since comics contains images and texts, this medium quickly attracted EFL students' attention (Januarty & Azizah Nima, 2018). It also became a useful tool to foster students meaning-making and reading comprehension (McGrail, Rieger, & Doepker, 2017). Its positive use in EFL learning enhances the comics' popularity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since comics contains images and texts, this medium quickly attracted EFL students' attention (Januarty & Azizah Nima, 2018). It also became a useful tool to foster students meaning-making and reading comprehension (McGrail, Rieger, & Doepker, 2017). Its positive use in EFL learning enhances the comics' popularity.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the use of comics as a teaching medium could not guarantee the improvement of students' writing ability if the teachers have difficulties towards the medium. Fourth, McGrail et al (2017) found that comics was a powerful medium for enhancing decoding skills, which contained contextual clues. Empirically, these findings proved that there were some advantages and disadvantages to using comics as a teaching medium.…”
Section: Introductionmentioning
confidence: 99%
“…Bonny Norton (2003), among others, has illustrated what children get out of reading comic books. Norton highlights a common thread in comic book reception research: finding that comic books do something useful (Dorrell, Curtis, and Rampal 1995;McGrail et al 2018). This is not least prevalent in studies with a focus on education.…”
Section: Meaning Making and Comic Booksmentioning
confidence: 99%
“…In Guided reading activity, the teacher supports students to gain control over the process that lead to successful independent reading (Aitken et al, 2018). Teachers had positive perceptions towards the use of guided reading with their struggling readers and writers as it could help readers and writers develop their skills and motivation (McGrail et al, 2017). Similarly, students had good perceptions on using guided reading; it could help students to shape their reading comprehension (Hanke, 2014).…”
Section: Guided Readingmentioning
confidence: 99%